Switching techniques for quasi-square-wave modulated modular multilevel converters in DC-DC conversion and motor drive systems - Xia, Peizhou (The University of Edinburgh, 2025)
The Modular Multilevel DC Transformer (MMDCT), originating from the Modular Multilevel Converter (MMC), offers a promising solution for high-power, high-gain DC-DC conversion, effectively addressing challenges such as high power semiconductor voltage ratings and dv/dt stress in conventional two-level Dual-Active-Bridge (DAB) topologies. This thesis investigates the design, optimization, and experimental validation of MMDCT, aiming to enhance its performance and efficiency. A comprehensive analysis is conducted on the transient behavior of MMDCT under Quasi-Square-Wave (QSW) modulation, providing insights into potential voltage mismatches, component sizing, and voltage estimation. However, the investigation reveals that the implementation of MMDCT introduces significant frequency-related losses due to the energy stored in arm inductors. To address this, an alternative switching sequence is proposed to recover the inductor energy and enable MMDCT operation at high switching frequencies. Additionally, this thesis presents the utilization of sub-module capacitance as snubber components to achieve zero-voltage switching (ZVS) and suppress voltage overshoot during high-current operations. The coordinated use of these switching techniques improves conversion efficiency and optimizes MMDCT performance. Moreover, this thesis incorporates the proposed inductor energy recovery switching technology into the QSW-modulated MMC inverter. This method enhances efficiency and eliminates the need for high-frequency current control, thereby simplifying the control requirements of the QSW-modulated MMC inverter. The design and implementation of a scaled experimental platform are presented, enabling the validation of theoretical findings and proposed control strategies under practical conditions. Experimental results demonstrate significant improvements in converter efficiency, voltage control, and overall performance.
Keywords: Modular Multilevel DC Transformer; MMDCT; efficiency; switching strategy; snubbers; energy recovery techniques; MMC inverter